The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1128/jb.179.21.6633-6639.1997
|View full text |Cite
|
Sign up to set email alerts
|

Propanediol utilization genes (pdu) of Salmonella typhimurium: three genes for the propanediol dehydratase

Abstract: The propanediol utilization (pdu) operon of Salmonella typhimurium encodes proteins required for the catabolism of propanediol, including a coenzyme B 12 -dependent propanediol dehydratase. A clone that expresses propanediol dehydratase activity was isolated from a Salmonella genomic library. DNA sequence analysis showed that the clone included part of the pduF gene, the pduABCDE genes, and a long partial open reading frame (ORF1). The clone included 3.9 kbp of pdu DNA which had not been previously sequenced. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
183
0
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(195 citation statements)
references
References 40 publications
6
183
0
6
Order By: Relevance
“…While these may still be intact MCPs, another potential explanation is that the MCPs and the reporter protein formed aggregates. In agreement with this latter hypothesis, a time course of cells expressing PduP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] -GFP in the absence of MCP induction shows diffuse fluorescence for several days, and also shows potential aggregation after eight days, as seen by the emergence of fluorescent puncta (Supporting Information 2, Fig. S1).…”
Section: Mcp Integrity Over Timesupporting
confidence: 72%
See 1 more Smart Citation
“…While these may still be intact MCPs, another potential explanation is that the MCPs and the reporter protein formed aggregates. In agreement with this latter hypothesis, a time course of cells expressing PduP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] -GFP in the absence of MCP induction shows diffuse fluorescence for several days, and also shows potential aggregation after eight days, as seen by the emergence of fluorescent puncta (Supporting Information 2, Fig. S1).…”
Section: Mcp Integrity Over Timesupporting
confidence: 72%
“…3 In the first two steps of the Pdu pathway, the substrate 1,2-PD is converted by the enzyme PduCDE to propionaldehyde, which is then converted to propionyl-CoA by PduP. 4,5 It is proposed that these first two steps within the Pdu MCP are encapsulated in order to sequester the toxic intermediate propionaldehyde. 6 The MCP shell, approximately 125-175 nm in diameter, is made up of thousands of copies of protein subunits, of which there are nine different types [ Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The inoculum was a 5-ml Luria-Bertani broth culture, and incubation was at 37°C with shaking at 275 rpm. Under these conditions, growth is supported by succinate but the 1,2-PD is not metabolized, assuring continued high induction of the pdu operon (10,15). After cultures reached late log phase (optical density at 600 nm between 1 and 1.2), cells from 2 liters of medium were harvested by centrifugation at 4,000 ϫ g for 10 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Surprisingly, these changes have provided a substantial clue to potential areas of adaptation having occurred in genes responsible for propanediol utilization (pduF) and propanediol diffusion facilitator (pudB) genes. Interestingly, propanediol is a metabolite resulting from ripening or rotting of plant tissues (Bobik et al, 1997;Brandl et al, 2013;Goudeau et al, 2013). Previous studies revealed that populations of mutants deficient in propanediol utilization were several logs lower than wild-type strains grown in cilantro (Goudeau et al, 2013).…”
Section: Microbial Adaptation On Produce Commoditymentioning
confidence: 99%